2019
DOI: 10.1371/journal.pone.0216181
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous diffusion for neuronal growth on surfaces with controlled geometries

Abstract: Geometrical cues are known to play a very important role in neuronal growth and the formation of neuronal networks. Here, we present a detailed analysis of axonal growth and dynamics for neuronal cells cultured on patterned polydimethylsiloxane surfaces. We use fluorescence microscopy to image neurons, quantify their dynamics, and demonstrate that the substrate geometrical patterns cause strong directional alignment of axons. We quantify axonal growth and report a general stochastic approach that quantitativel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(79 citation statements)
references
References 45 publications
(195 reference statements)
4
73
0
Order By: Relevance
“…The cells used in this work are cortical neurons obtained from embryonic day 18 rats. For cell dissociation and culture, we have used established protocols presented in our previous work [ 10 , 15 , 16 , 19 , 20 , 30 , 31 , 32 ]. In our previous work, we have performed immunostaining experiments that show high neuron cell purity in these cultures [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The cells used in this work are cortical neurons obtained from embryonic day 18 rats. For cell dissociation and culture, we have used established protocols presented in our previous work [ 10 , 15 , 16 , 19 , 20 , 30 , 31 , 32 ]. In our previous work, we have performed immunostaining experiments that show high neuron cell purity in these cultures [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…These studies have shown that neurons grown on substrates with periodic geometrical features develop different growth patterns when compared to neurons grown on surfaces lacking a periodic geometry. Such differences include populations of axons that are significantly longer and that tend to align their growth with preferred spatial directions [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations